The repayment of bank credits having financed investments in the Domar model - Cottin-Euziol, Edouard (Brazilian Keynesian Review, 2015)
In the Domar model, based on the Keynesian multiplier theory, investment generates savings. Therefore, savings cannot fund investments, at least ex ante. Investments have first to be financed by bank credit, hence the question on their repayment. In this article, we suppose that investments are financed by bank credits issued on several periods, as it typically takes years for firms to reimburse their investment debt. What we then obtain is that, in order to avoid an overproduction crisis, the rate of capital accumulation has to gradually rise throughout a growth phase. This result paves the way to a theory of cycles based on the repayment of bank credits.